ChemInform Abstract: Type II Intramolecular [5 + 2] Cycloaddition: Facile Synthesis of Highly Functionalized Bridged Ring Systems. Issue 25 (5th June 2015) - Mei, Guangjian; Liu, Xin; Qiao, Chuang; Chen, Wei; Li, Chuang‐chuang
Abstract: The first type II intramolecular [5 + 2] cycloaddition reaction involving an oxopyrylium ylide and a simple alkene provides a range of bridged cycloheptenone derivatives.